Phosphorus forms and distribution in Andisol under contrasting land-use systems in central Mexico - Tinoco-Varela, Daniel; Bayuelo-Jiménez, Jeannette S. (REVISTA TERRA LATINOAMERICANA, 2021)
Conversion of forest to conventional farming systems may affect phosphorus (P) distributions and availability, particularly in P-limited soils. The objective of this study was to evaluate the effect of land use (native forest and avocado farming systems) on forms, distribution, and availability of P in soil. Soil samples (Andisol) from three sites cultivated with conventional farming and others from a contiguous native pine forest area were included. Soil Po and Pi fractions and microbial P were sequentially extracted after seven and 28-days (d) of incubation, respectively. In cultivated soil, total P was mostly represented by inorganic fractions (66 to 78%). Pi was mainly composed of easily mineralized P (Bic-Pi), moderately stable (NaOH0.1-Pi) and relatively insoluble fractions (Residual-Pi). However, Po proportion (29%) decreased under cropped soil due to depletion of soil organic matter. In contrast, in native forest soils, more than 48% of P was extracted in microbial biomass, Bic-Po, and NaOH0.1-Po fractions. The distribution of soil P fractions was associated with soil use type. Conventional farming systems stimulated P retention in Fe-Al oxides (NaOH0.1-Pi and Residual-Pi) and decreased P availability. Compared to cultivated soil, the higher organic P proportion under forest corresponded to higher organic matter (OM) and microbial P, which highlights the potential relevance of SOM and microbial P in sustaining P availability in P-limited acidic soils. Sustainability in cropped systems could be enhanced by promoting adequate management practices aimed at increasing soil organic P storage and reducing soil chemical reactions that absorb, occlude or precipitate applied inorganic P.